Lingual and Sublingual Haematoma in a Patient Following Streptokinase Administration in Acute Myocardial Infarction- A Case Report - Alam, Shoaeb Imtiaz; Md Jamil, Abu Bakar; Parvin, Tanjima; Mahbub, SM Ear E; Siddique, Md Abu (Cardiovascular Journal, 2017)
The value of thrombolysis by Streptokinase administration in the treatment of acute myocardial infarction is well established. Haemorrhage is a common complication of fibrinolytic therapy. Here, we report an unusual case of spontaneous lingual and sublingual haematoma following streptokinase therapy after acute myocardial infarction. A 57-year-old man with a diagnosis of acute ST elevated myocardial infarction treated with streptokinase developed a large lingual and sublingual haematoma. Though his airway was not compromised, he had difficulty in swallowing. A conservative approach was made by starting parenteral nutrition, preventing rethrombosis by not reversing the action of streptokinase as his coagulation profile was within normal limits and maintaining optimum blood pressure, blood glucose level and urine output. His tongue swelling subsided after four days and oral medication and feeding was started. No complication occurred during this period. Though there is no adequate information regarding the management of the patient, a vigilant monitoring of the patency of the airway with a conservative approach by not reversing the effect of streptokinase and preventing coronary rethrombosis may produce a better outcome in such cases. Cardiovasc. j. 2017; 10(1): 97-100